Effects of Macrosegregation and Microstructure on the Corrosion Resistance and Hardness of a Directionally Solidified Zn-5.0wt.%Mg Alloy - Vida, Talita Almeida; Soares, Thiago; Septimio, Rudimylla Silva; Brito, Crystopher Cardoso; Cheung, Noé; Garcia, Amauri (Materials research (São Carlos, São Paulo, Brazil), 2019)
This study aims to analyze the influence of macrosegregation on microstructure evolution, and of microstructure length scale on the corrosion resistance of a Zn-5.0wt.%Mg alloy casting. The analyzed samples were taken along the length of castings unidirectionally solidified in unsteady state conditions of heat extraction. Microstructure characterization, microhardness, linear polarization and electrochemical impedance spectroscopy (EIS) tests were performed. A unique type of microstructure was observed, characterized essentially by a morphology typified by idiomorphic MgZn2 crystals in a “complex eutectic mixture” [coexistence of stable (Zn+Mg2Zn11) and metastable (Zn+MgZn2) eutectics]. The correlation between thermal and microstructural parameters, permitted experimental growth laws, correlating the evolution of the lamellar eutectic spacing with the cooling rate to be established. Vickers microhardness and electrochemical corrosion tests showed that more refined microstructures associated with higher experimental cooling rates, are related to a better set of higher hardness and corrosion resistance.